A study on AC system stabilization using corrective control of embedded DC systems. Issue 4 (2019) - Yoon, Minhan; Lee, Jaehyeong; Hwang, Sungchul; Jeong, Soseul; Kim, Jongan; Jang, Gilsoo
Abstract: DC systems do not control power flow by themselves for system disturbances unlike AC systems. If this control is not done properly, it can become an unstable factor in the power system operation. In this paper, the method to improve the stability of AC system through proper control of embedded DC system installed in complex AC system has been studied. The method and procedure for utilizing the SCADA system to ensure that the DC system is properly controlled for N-1 contingencies are proposed. The system identifies the overloaded line through SCADA and calculate the operating point of the DC system to minimize the overload of the transmission line. This signal is sent to the master controller of the DC system to perform overload suppression. The method and procedures have been verified through the PSS/e dynamic simulation using real power system data.